Development Of Animation Videos To Improve Nutrition Awareness Of Elementary School Students In Rantau Rasau District - Prasetio, Dedi; Sukendro, Sukendro; Anjanika, Yonifia (UNIVERSITAS NEGERI MAKASSAR, 2025)
The development of animated videos as a learning media for nutrition for elementary school students in the Rantau Rasau District has proven to be effective and feasible to use. This is supported by several important findings. First, the validation results showed very good quality, with the assessment of media experts reaching a value of 46 and material experts reaching a value of 45 (both in the